Comparative analysis of detoxification-related gene superfamilies across five hemipteran species - Volonté, Mariano (2022)
Hemiptera is one of the most speciose orders of insects, and the most speciose considering Hemimetabola. Through their evolutive history, hemipterans with different feeding habits have adapted to deal with different chemical challenges. Three major gene families are involved in xenobiotic detoxification in insects: the cytochromes P450 (CYPs), carboxyl/cholinesterases (CCEs), and glutathione transferases (GSTs). Here we perform a comparative analysis on the complement of these gene superfamilies across five hemipteran species; four heteropterans (the pentatomid plant feeders Nezara viridula and Halyomorpha halys; the hematophagous Cimex lectularius, Cimicidae, and Rhodnius prolixus, Reduviidae), and one Auchenorrhyncha plant feeder (Nilaparvata lugens).